Dorothy Bohm at 100 a life in photography - Bohm, Dorothy 1924-2023; Bohm-Duchen, Monica; Barron, Katy (Beam Editions, 2024)
Exploring the work of one of the most prolific, versatile and admired female photographers of the 20th century, Dorothy Bohm at 100 takes a fresh look at the photographer's 75-year-long career, showing a selection of her most iconic images alongside many previously unpublished works. Born in 1924 into a Jewish family in East Prussia, Dorothy Bohm was sent to the safety of England in 1939. Her experience of war and dislocation deeply influenced her photographic approach, one that displays a fascination with people from all walks of life, particularly women and children. After training in studio portraiture in 1940s Manchester, Bohm travelled extensively in the post-war period, establishing herself as a leading humanist street photographer. The mid-1980s saw a shift as Bohm started working exclusively in colour, infusing her images with texture and spatial ambiguity, evoking the human presence in increasingly abstract, complex and allusive forms. This new volume, published to mark the centenary of Bohm's birth, showcases the diversity of her work and her profound empathy for the human condition. The book features essays by Martin Barnes, Senior Curator of Photographs, Victoria & Albert Museum, photographer and writer Rachel Wallace, a biographical essay by art historian Monica Bohm-Duchen, and short texts by a wide range of notable contributors, each focussing on a single photograph. -- Publisher
Includes biography and exhibition history
With contributions from: Maria Balshaw, Martin Barnes, Katy Barron, Monica Bohm-Duchen, Colin Ford CBE, Anna Fox, Lydia Goldblatt, Mark Haworth-Booth, Amanda Hopkinson, Ian Jeffrey, Esther Leslie, Markéta Luskačová, Don McCullin, Pelumi Odubanjo, Martin Parr, Nissan N. Perez, Marissa Roth, Paul Smith, George Szirtes, Rachel Wallace, Marina Warner, Val Williams
Includes bibliographical references (page 237)
Keywords: Bohm, Dorothy -- 1924-2023; Bildband